EFEKTIFITAS PELATIHAN ”SAYA SEHAT, SEMUA SEHAT” UNTUK MENIGKATKAN KESADARAN TERHADAP PENYAKIT HEPATITIS A PADA MAHASISWA - Pramono, Ridwan Budi (Universitas Ahmad Dahlan, 2015)
AbstractHepatitis A is a disease caused by a virus of hepatitis A. College students is a group have highest risk exposed this disease. The objective of this research is to know whether the method of the training called “sayasehat, semuasehat” is effective increasing awareness for the college students with the efforts to decrease the risk of hepatitis A. The subject of the research are twenty students. The criteria are the students who often buy food in street foodstall. The subject were the students who live in the dormitory or in boarding house and willing to follow the training. They fulfil ledwritten informed consent to follow the four sessions training. This research uses pretest and postest control group design. The data was analyzed using anava mixed design. The intervention of this research was training called“saya sehat, semua sehat”. The result shows that the training of “saya sehat, semua sehat”, were able to increase the college students’ awareness againts hepatitis A. The increase significantly happened in experiment group. The awareness of the college students againtshepatitis A increases 57,7%.Keywords: awareness, hepatitis A, trainin